Enzymological Effects of Lead Acetate Exposure in Various Organs of Oreochromis mossambicus (Peters 1852) - Rose, R. Nisha; Lakshmanan, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The various enzymological effects of heavy metal Lead acetate (Pb(C2H3O2)2) exposed to fingerlings of Oreochromis mossambicus was analyzed in this study. The 30 days old fingerlings of O. mossambicus were exposed to sub lethal dose 3.80ppm of 96 hrs. LC50 of Pb(C2H3O2)2 for 21 and 28 days, various organs (liver, gill, kidney and muscle tissue) were removed from control and treated fishes and were used for various enzymological effect: Succinate dehydrogenase (SDH), Lactate dehydrogenase (LDH), Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Acid phosphatase (ACP) and Alkaline phosphatase ALP). The observed data were subjected into various statistical analysis by using IBM-SPSS version 26. Among the two different exposure periods 21 and 28 days which compared with control fingerlings organs, the various enzymological effects were drastically suffered (Treated fish enzymological levels were inversely proportionate towards the control groups of fish species) by 28 days of exposure periods. Pb(C2H3O2)2 exposed to fingerlings which tested on various organs at 28 days interval periods for assessing of SDH, LDH, AST, ALT, ACP and ALP of various organs of treated fish: Liver: 12.02, 55.75, 58.24, 125.27,12.26, 11.82 µ moles of phenol liberated/ mg of protein; Gill: 10.80, 33.75, 28.73, 28.11, 7.80, 8.63 µ moles of phenol liberated/ mg of protein; Kidney: 12.18, 46.33, 44.78, 75.40, 6.27, 10.38 µ moles of phenol liberated/ mg of protein and Muscle: 11.72, 32.44, 32.76, 44.20, 3.72, 7.20 µ moles of phenol liberated/ mg of protein were recorded on tissue of treated fish. The enzymological effect of Pb(C2H3O2)2 exposed towards O. mossambicus which observed various health defects on organism exposed to a particular toxicant. It may give sufficient information about heavy metal contamination on aquatic organism and would help us to propose policies to protect the ecosystem.